2018
DOI: 10.1177/1742271x17751255
|View full text |Cite
|
Sign up to set email alerts
|

Levels of agreement in the measurements of carotid artery ultrasound across a regional vascular network

Abstract: This study highlights the difficulty in obtaining consistent velocity measurements from a subject. Despite the variability in absolute peak systolic velocity and end diastolic velocity, scientists were generally consistent in obtaining an optimal spectral Doppler trace. Some issues with consistency were, however, identified which were subsequently addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Moreover, we found that the significance of this association increased as a function of the number of carotid plaques analyzed by ultrasound, and we also provide a specific set of proteins that were associated with diffuse atherosclerosis (3+ plaques). Indeed, we identified 87 proteins, which associated with the presence of three or more plaques, presenting either a reduced (5) or increased (82) plasmatic expression compared to controls. By contrast, plasma proteomics was not able to significantly discriminate neither the subjects presenting with 2 or with just one carotid plaque.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found that the significance of this association increased as a function of the number of carotid plaques analyzed by ultrasound, and we also provide a specific set of proteins that were associated with diffuse atherosclerosis (3+ plaques). Indeed, we identified 87 proteins, which associated with the presence of three or more plaques, presenting either a reduced (5) or increased (82) plasmatic expression compared to controls. By contrast, plasma proteomics was not able to significantly discriminate neither the subjects presenting with 2 or with just one carotid plaque.…”
Section: Discussionmentioning
confidence: 99%
“…However, applying noninvasive vascular imaging procedures to detect subclinical ACVD, such as those identifying carotid plaques, is challenging in “apparently healthy” population, owing organizational, economical barriers, and given the substantial shortcomings in sensitivity and inter-operator variability 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…According to Loizou et al (2015), people who have not undergone cardiovascular changes do not present differences between left and right IMT. Atherosclerotic plaques deposited in the common carotid arteries are not as frequent in animals as they are in humans, where considered one of major causes of mortality in the world (Mendis et al 2011, Ricotta et al 2011, Barlinn et al 2018, Boyko et al 2018, Evans et al 2018, Mckenna et al 2018, Oglat et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler ultrasonography is a tool combined with B-mode ultrasonography that allows the hemodynamic evaluation of the vessels (Loizou 2014, Barlinn et al 2018, Boyko et al 2018, Mckenna et al 2018, Oglat et al 2018. The common carotid artery originates three important arteries in horses and mules: the internal carotid artery, the external carotid artery and the occipital artery.…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial variability from laboratory to laboratory in the CDUS thresholds and derived indices applied to diagnose and grade CS (56)(57)(58)(59)(60). Even among accredited vascular testing centers, the diagnostic thresholds for CS severity vary considerably (60).…”
Section: Diagnostic Criteria For Extracranial Carotid Artery Stenosismentioning
confidence: 99%